PENDIDIKAN KATOLIK DI KEUSKUPAN AMBOINA: Kenyataannya Kini dan Harapan di Masa Akan Datang - Mandagi, P.C. (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2012)
The purpose of Christian education is to bear human quality in all its apects. This paper is the a reflection of the situation of Catholic education in the Diocese of Amboina. It argues that the diocese has implemented the call and mission to be a sacrament of God’s salvation to the world through the work of education within families and the Catholic Schools, yet, it still need to be addressed and improved in the future. Then, what should be done? In this context, it needs a cooperation of all parties to reform the existing management of the Catholic Schools in order to bear a quality of human and Christian persons.